Characterisation of Physicochemical Properties of Propionylated Corn Starch and Its Application as Stabiliser - Hong, Lee Fen; Cheng, Lai Hoong; Chong, Yew Lee; Kok, Khiang Peh (University of Zagreb, 2015)
A series of propionylated starches with diff erent degrees of substitution (DS) was synthesised and their physicochemical properties and application as a stabiliser were investigated. Starch propionates with moderate DS were prepared by esterifi cation of native corn starch with propionic anhydride. By varying the reaction times of the esterifi cation process, twelve starch propionates with DS of 0.47 to 0.94 were prepared. FTIR and NMR confi rmed the introduction of propionyl groups to the starch. X-ray diff raction patt ern showed reduced crystallinity in the starch propionates. The contact angle was found to increase proportionately with the increase in DS. Swelling power results showed that starch propionates were able to swell more than native corn starch at low temperature (40 °C). Oil-in- -water (O/W) emulsions prepared using starch propionates (DS of 0.64 to 0.86) showed exceptional stability when challenged by centrifugation stress test. These stable O/W emulsions had viscosities in the range of 1236.7–3330.0 mPa·s. In conclusion, moderately substituted short-chain (propionylated) starches could be a promising cold swelling starch, thickener and O/W emulsion stabiliser in food, pharmaceutical and cosmetic industries.